Laboratory and field evaluation of the insect growth regulator pyriproxyfen (Sumilarv 0.5 G) against dengue vectors - Vythilingam, I.; Luz, B.M.; Hanni, R.; Beng, T.S.; Huat, T.C. (2005)
The insect growth regulator pyriproxyfen was tested against Aedes aegypti at 0.01 and 0.02 mg of active ingredient (AI) per liter of water in 60-liter earthern jars. Both concentrations provided 100 control for 4 months. In additional experiments where 10 liters of water were replaced fortnightly, 100 control was still obtained over 4 months with 0.02 mg AI/liter and greater than 93-100 control was obtained over 4 months with 0.01 mg AI/liter. In less-controlled field-trial conditions, pyriproxyfen at a dosage of 0.02 mg AI/liter provided 100 control for 10 wk against Aedes albopictus even though water was replaced either daily or weekly. Although the activity of pyriproxyfen declines after 10 wk, those tests in the plastic tubs showed much higher levels of sustained residual activity compared to those in the earthern jars. Pyriproxyfen did not have an impact on nontarget organisms.